A methods engineering study on Maple Leaf Enterprises - Florendo, Michael L.; Galang, Myrtle Holiday G.; Santos, Francis Harold G.; Turay, Dahlia G. (Diliman, Quezon City College of Engineering, 2002)
Maple Leaf Enterprises is a medium sized company involved in bag making industry. In the Philippines, bag making industry is a truly potential source of income. The group has decided to choose Maple leaf Enterprises with a hope of improving the existing condition of the said company and consequently contribute in the development of bag making industry in the Philippines. To be able to propose improvements, the techniques in Methods Engineering will be the basic analytical tools. Based from the group's observations and analysis and interviews from workers and the management, Maple Leaf Enterprises still has areas to improve. Using the Streamline Diagnosis Diagram, it was found out that the Maple Leaf Enterprises' current flow of production is not properly designed due to the improper positioning of workstations and equipment and the improper sorting and storing of raw materials. To address these problems, two alternatives are proposed by the group, the first one being the better alternative. It includes the transferring of the cutting area to the office and rearrangement of the Quality Control Area and Production Supervisor's Area. In addition, the functions of the Quality Control Department are reassessed and separated in two : packaging and inspection. The criteria for evaluating the alternatives are classified as either quantitative or qualitative. The criteria under quantitative are total travel distance, frequency of trips, number of delays, cost and efficiency in supervision of operations. On the other hand, linearity in workflow is under the qualitative area. The tools used to come up with alternatives are Flow Process Chart, Flow Diagram, Distance Matrix, Trip Frequency Matrix and Interaction of Workstations Matrix. The group recommends that the layout for alternative one be implemented. Only minor changes are required, therefore, a day would be sufficient for the rearrangement and transferring of the equipment. Four workers will be assigned for the job. A Gantt chart and a Load Chart were used to illustrate the activities that have to be accomplished by the respective workers. For future proponents, the group recommends that other layouts that can further improve the process flow be considered. Furthermore, a study focusing on man, which is another problem identified in the Streamline Diagnosis Diagram, can be conducted. A stricter implementation of the policies would be of much help to the company. Moreover, the company is encountering problems with their scraps. This concern can also be addressed by future proponents.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Maple Leaf Enterprises; Luggage industry; Systems analysis